Antithrombotic Therapy in Chronic Total Occlusion Interventions - Iosif Xenogiannis; Charalampos Varlamos; Despoina-Rafailia Benetou; Dimitrios Alexopoulos (US Cardiology Review, 2021)
Chronic total occlusion (CTO) recanalization is among the most complex subsets of coronary interventions. Hence, optimum peri- and post-procedural anticoagulation and antiplatelet therapy is key for the achievement of successful revascularization and reduction of major adverse cardiovascular outcomes in patients undergoing CTO percutaneous coronary intervention (PCI). Unfractionated heparin is still considered the gold standard anticoagulant because its action can be reversed by protamine administration, with bivalirudin being reserved mainly for patients with heparin-induced thrombocytopenia. However, small studies comparing unfractionated heparin with bivalirudin in CTO interventions have shown similar outcomes. Glycoprotein IIb/IIIa inhibitors should, in general, be avoided. Aspirin in combination with clopidogrel for 6–12 months is the standard post CTO PCI dual antiplatelet regimen. For the most complex cases, clopidogrel can be substituted by a more potent P2Y12 inhibitor, namely ticagrelor or prasugrel.